2018
DOI: 10.1111/plb.12909
|View full text |Cite
|
Sign up to set email alerts
|

The role of hybridization and introgression in maintaining species integrity and cohesion in naturally isolated inselberg bromeliad populations

Abstract: Hybridization is a widespread phenomenon present in numerous lineages across the tree of life. Its evolutionary consequences range from effects on the origin and maintenance, to the loss of biodiversity. We studied genetic diversity and intra- and interspecific gene flow between two sympatric populations of closely-related species, Pitcairnia flammea and P. corcovadensis (Bromeliaceae), which are adapted to naturally fragmented Neotropical inselbergs, based on nuclear and plastidial DNA. Our main results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…Here, as in other species (i.e., Mota et al, 2019), P. exserta is kept as a unique evolutionary unit, independently from P. axillaris, but contrarily to those Bromeliads, the gene exchange is not low between Petunia species in Serra do Sudeste (see Turchetto et al, 2019b). P. exserta can be considered narrowly endemic compared to P. axillaris and, in general, has lower diversity indices than its sister species even accounting only sympatric populations (Lorenz-Lemke et al, 2006;Segatto et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Here, as in other species (i.e., Mota et al, 2019), P. exserta is kept as a unique evolutionary unit, independently from P. axillaris, but contrarily to those Bromeliads, the gene exchange is not low between Petunia species in Serra do Sudeste (see Turchetto et al, 2019b). P. exserta can be considered narrowly endemic compared to P. axillaris and, in general, has lower diversity indices than its sister species even accounting only sympatric populations (Lorenz-Lemke et al, 2006;Segatto et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, species complexes and non-monophyletic species are common in plants (Naciri & Linder, 2015;Pinheiro, Dantas-Queiroz & Palma-Silva, 2018) and are thought to be the result of hybridization or incomplete lineage sorting. Assuming that post-zygotic barriers for reproduction of bromeliads are potentially weak (Palma-Silva et al, 2011;Wagner et al, 2015) and that the individuals often grow in mixed aggregates of species sharing the same pollinator, interspecific gene flow may occur and lead to the formation of natural hybrids (Palma-Silva et al, 2011;Lexer et al, 2016;Zanella et al, 2016;Neri, Wendt & Palma-Silva, 2017;Mota et al, 2019). Furthermore, natural hybrids of closely related Vriesea spp.…”
Section: Phylogenetic Relationships In Vrieseamentioning
confidence: 99%
“…Hybridization is also thought to have promoted bromeliad diversity (Palma-Silva et al, 2016) but although both artificial (Vervaeke et al, 2004;Wagner et al, 2015;de Souza et al, 2017) and natural hybrids have been reported (e.g., Palma-Silva et al, 2011), the frequency and exact contribution of this phenomenon to bromeliad diversity are still to be determined. While some studies suggest that hybridization generates intraspecific genetic diversity in isolated populations (Lexer et al, 2016;Neri et al, 2018;Mota et al, 2019), it may also prevent genetic differentiation and blur species boundaries (Goetze et al, 2017). To date, most of the research on hybridization in bromeliads focuses on the population level and studies with a macroevolutionary perspective are lacking.…”
Section: Introductionmentioning
confidence: 99%